Prolonged Mechanical Ventilation Predictors in Patients Undergoing Liver Transplantation - Meltem Güner CAN; Ali ÖZER (Bezmiâlem Science, 2019)

(untitled)
Objective:Liver transplantation is the current treatment modality for end-stage liver disease. While there is increasing drive towards early extubation in patients undergoing liver transplantation, prolonged meachanical ventilation (PMV) related to various factors can be observed. We tried to determine the risk factors associated with PMV.Methods:One hundred twenty five patients (age>18 years) of with the American Society of Anesthesiology (ASA) III-IV group undergoing liver transplantation were enrolled in this retrospective study. Patient charts, intraoperative and intensive care unit followup forms, and electronic medical recording system were used for data collection. Patients were categorized as having received (with) or not received (without) prolonged mechanical ventilation (>24 hours), and perioperative risk factors were attempted to determine.Results:No significant intergroup differences were found in demographic variables but ASA and model for end-stage liver disease (MELD) scores were significantly higher in the with-than in the without-PMV group. Total amount of suspension of erythrocytess suspension, fresh frosen plasm, and cell-saver blood used intraoperatively was higher in the with-PMV group but difference did not reach statistical significance. Patients with-PMV had significantly higher cryoprecipitate transfusion rates than did those without-PMV (p=0.007). While no significante intergroup differences were found in mortality and lenght of hospital stay; lenght of intensive care unit (ICU) stay was higher in the with-PMV group (p=0.001). Extravascular lung water index, global ecosystem dynamics ınvestigation, and pulse volume index values obtained from pulse contour cardiac output (PiCCO) monitorization were significantly lowver in the with- than in the without-PMV group.Conclusion:We found that preoperative high ASA and MELD scores, high blood product transfusion rates, and hypovolemia supported by the PiCCO measurements are were closely related to PMV and long lenght of ICU stay.